2020
DOI: 10.2196/21475
|View full text |Cite
|
Sign up to set email alerts
|

Digital Pain Mapping and Tracking in Patients With Chronic Pain: Longitudinal Study

Abstract: Background Digital pain mapping allows for remote and ecological momentary assessment in patients over multiple time points spanning days to months. Frequent ecological assessments may reveal tendencies and fluctuations more clearly and provide insights into the trajectory of a patient’s pain. Objective The primary aim of this study is to remotely map and track the intensity and distribution of pain and discomfort (eg, burning, aching, and tingling) in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 74 publications
1
12
0
Order By: Relevance
“…In accordance with previous reports that have shown that patients with chronic pain are strongly interested and eager to use a digital health-based mobile app, we found that a large percentage of patients undergoing an SCS trial, if offered, are willing to use such a tool [ 4 , 6 , 8 ]. Given the importance the trial phase can have on the decision to proceed with permanent implantation of an SCS device, this sizable rate of user participation demonstrates the potential viability of a mobile tracking app to improve the utility of an SCS trial.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In accordance with previous reports that have shown that patients with chronic pain are strongly interested and eager to use a digital health-based mobile app, we found that a large percentage of patients undergoing an SCS trial, if offered, are willing to use such a tool [ 4 , 6 , 8 ]. Given the importance the trial phase can have on the decision to proceed with permanent implantation of an SCS device, this sizable rate of user participation demonstrates the potential viability of a mobile tracking app to improve the utility of an SCS trial.…”
Section: Discussionsupporting
confidence: 91%
“…More importantly, these contemporary tools have been demonstrated to help instill a greater level of assurance in patients, that their pain condition can be controlled. These devices can also promote improved self-monitoring of the multidimensional experience of chronic pain, and some concurrently allow health care providers enhanced connectivity to real time outcomes reported by those under their care [ 4 - 6 ]. The implementation and use of new digital methodologies in the context of health care is underpinned by what is now referred to as ecological momentary assessment (EMA), an approach constituted by the frequent sampling of study subjects’ behavior, outcomes, and experiences in real time within the real-world environments in which they live and participate [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In various pain conditions, an increased pain area is related to higher pain intensity and disability (Lluch Girbés et al, 2016;Boudreau et al, 2017;Galve Villa et al, 2020;Miró et al, 2014Miró et al, , 2017Barbero et al, 2017). Similarly, a larger area of groin pain based on pain drawings is positively associated with groin pain intensity, the number of clinical entities, and the presence of bilateral symptoms in athletes with longstanding groin pain (Serner et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it will make pain assessment more accurate and efficient to enhance easy tracking of patient response to treatment. This method can be applied to patients with acute 21 or chronic 22 pain longitudinally using any digital records at no cost and yet produce accurate results. Because of advantages in momentary assessment of pain, there may be no variability of pain location, but increasing BSA could indicate progression in the cause of pain and alert the nurse to take appropriate action to treat the cause of pain.…”
mentioning
confidence: 99%
“…In previous studies, investigators examined the association between the number of pain locations with other pain variables (eg, pain intensity, duration, and quality), 23,24 negative disease outcomes such as disability, 18 and pain centralization. 7 Digital pain drawings are receiving increased attention 21,22 because of the aforementioned advantages to improve pain assessment and management. Pain distribution and location, however, have not been measured frequently due to multiple reasons.…”
mentioning
confidence: 99%